Plant production for biomass into energy: economics and energy efficiency view - Wajszczuk, Karol; Wawrzynowicz, Jacek; Pepliński, Benedykt (Applied Studies in Agribusiness and Commerce, 2016)
The aim of the paper was to determine the influence of the fertilization level on the energy and economics efficiency of the production technologies of selected crops processed into bioethanol or biogas. There were investigated the following crops: rye, triticale, wheat, sugar beets, maize, sorghum, reed canarygrass and Virginia fanpetals. In the energetic efficiency the Energy Return on Energy Investment index (EroEI) was used. Apart from the ERoEI ratio, the Net Energy Value (NEV) ratio was also used. In the economics efficiency attitude, the Gross Margin (GM) was determined.The investigations proved that in general, the production technologies of crops where the lowest levels of nitrogen fertilization were applied proved to have the highest energetic efficiency. The highest economic efficiency was characterized by the production of corn for biogas. In the case of the production of bioethanol (all plants), ratios were on the verge of profitability or the lack of it showed.The analysis proved that the efficiency of the technologies of production of the crops to be processed into biogas is several times higher than the energetic efficiency of the technologies of production of the crops to be processed into bioethanol.